Keterampilan Pengolahan Umbi Gembili Menjadi Produk MPASI Melalui Sekolah Kader Sehat - Aditya Fajar Cahyono Putra; Thoha Syaifudin Zuhri; Aninda Diar Aulia; Rizqi Nuraini; Royani Eka Safitri; Aan Sofyan (Abdi Geomedisains, 2023)
Gembili (dioscorea esculenta l. burkill) is one of the discoreacea family of bulbous umbers, one of the bulbs that has a high nutritional content and contains high amounts of food and carbohydrates and low amounts of fat (utami etc. , 2013). But the gemstone in jatisari village is still underutilized into a functional food source that can provide higher selling value and increase the nutritional content of food products, especially mpasi or other food products, such as porridge, nugget and cookies. A method used in a community devotion activity of public speaking, practice, and question-and-answer. The performance of public service is in three stages, including the preparation, execution and final or evaluation. The total value of the PKK women's test was 88.94, and the average for the post test for jasitasari village is 90.52. So it can be concluded that the knowledge of 19 PKK women participants from before being given counseling material to after being given counseling material has increased. This healthy cadre school is expected to be one of the solutions in processing gembili tubers into MPASI products, to help meet baby nutrition and have a higher selling value, improve the economy of PKK mothers in Jatisari village.